Ai, Ethics, and Law: Who is Responsible? - Martinelli, Imelda; Limmartin, Tesalonika Valerie; Daya, Priscilla Angelia; Safrico, Hierico Misael; Patricia, Meilody (Universitas Syiah Kuala, 2025)
In Indonesian law, only humans and legal entities are recognized as legal subjects. The development of AI capable of independent thought and action raises new issues when its actions cause harm, because AI is not yet recognized as a legal subject. As a result, civil liability for AI actions remains unclear and creates a legal vacuum. This study aims to analyze the relationship between AI, ethics, and law in the context of liability for actions generated by artificial intelligence systems. The research method is normative with a comparative approach, comparing legal policies in several countries that have begun to formulate a legal framework for AI, such as the European Union, the United States, Japan, and South Korea. The results of the study show that Indonesia needs to immediately establish specific regulations governing the legal status and responsibility of AI in the realm of civil law. This law is expected to provide legal certainty, protect the rights of the people, and create a balance between technological progress and the principles of legal justice